This infinite system of linear equations:

$$ \begin{array}( 2x_1=1 \\ 3x_1+4x_2=2 \\ 4x_1+5x_2+6x_3=3 \\ \cdots \end{array} $$

In other words, this is particular case of a system:

$$ \begin{array}( a_{11}x_1=b_1 \\ a_{21}x_1+a_{22}x_2=b_2 \\ a_{31}x_1+a_{32}x_2+a_{33}x_3=b_3 \\ \cdots \\ a_{m1}x_1+a_{m2}x_2+ \cdots + a_{mn}x_n + \cdots=b_m \\ \cdots \end{array} $$

With the coefficients given by:

$$a_{mn}=m + n~~~~~~~~~b_m=m$$

The systems seems to give the following sequence of solutions:

$$x_n= \left| \left( \begin{matrix} \frac{1}{2} \\ n \end{matrix} \right) \right|=\left(\frac{1}{2}, \frac{1}{8}, \frac{1}{16}, \frac{5}{128}, \cdots \right)$$

How can I prove that it's true?

Why does it happen? Can other fractional binomial coefficients be obtained this way (and how)? By 'this way' I mean a triangular system with simple regular sequence of integer coefficients.

I had some thoughts, and that's what I tried. Let's assume, that $x_n$ I found are really binomial coefficients. Then for $x_m$ we will have:

$$x_m= \left| \left( \begin{matrix} \frac{1}{2} \\ m \end{matrix} \right) \right|=\frac{1/2 (1-1/2)(2-1/2)\cdots (m-1-1/2)}{m!}=\frac{m-3/2}{m}x_{m-1}$$

$$x_m= \left(1- \frac{3}{2m} \right)x_{m-1}=x_1-\frac{3}{2}\left(\frac{x_1}{2}+\frac{x_2}{3}+\cdots+ \frac{x_{m-1}}{m} \right)$$

$$x_m=\frac{1}{2}-\frac{3}{2}\left(\frac{x_1}{2}+\frac{x_2}{3}+\cdots+ \frac{x_{m-1}}{m} \right)$$

On the other hand, from the $m^{th}$ equation we can derive:

$$x_m= \frac{b_m}{a_{mm}}-\frac{1}{a_{mm}}\left(a_{m1}x_1+a_{m2}x_2+\cdots+ a_{m,m-1}x_{m-1} \right)$$

$$x_m= \frac{1}{2}-\frac{1}{2m}\left((m+1)x_1+(m+2)x_2+\cdots+ (m+m-1)x_{m-1} \right)$$

I don't see how to get this relation into the same form as the previous one. Maybe I should modify it somehow.

  • $\begingroup$ If you mean "in this way", yes. Every sequence can be produced as a solution to an infinite system of linear equations. $\endgroup$ – Christopher Carl Heckman Apr 18 '16 at 8:01
  • $\begingroup$ @CarlHeckman, I also meant 'how'? $\endgroup$ – Yuriy S Apr 18 '16 at 8:02
  • $\begingroup$ @CarlHeckman, also, could you please give me a reference for this statement? Where can I read about the connection between sequences and systems of linear equations? $\endgroup$ – Yuriy S Apr 18 '16 at 8:06
  • 2
    $\begingroup$ You're going to get mad ... Just look at the system $x_1=a_1$, $x_2=a_2$, $x_3=a_3$, etc. Otherwise, you need to clarify what you mean by "this way". $\endgroup$ – Christopher Carl Heckman Apr 18 '16 at 8:07
  • $\begingroup$ What are ${a_{mn}},\;{b_m}$? $\endgroup$ – user328032 Apr 18 '16 at 14:22

Since my hint in the comments was not followed up on, I'll elaborate in an answer.

Let $x_n = |\binom{\frac{1}{2}}{n}|$, and define:

$$A_m = (m+1)x_1+(m+2)x_2+\dots+ (m+m)x_m$$

What you are trying to show is that $A_m = m$ for all $m$. You already checked a few values that can be a base case for induction, so it will be enough to show that the sequences $A_1, A_2, \dots$ and $1,2,3...$ both satisfy the same recurrence.

The sequence $1,2,3,...$ satisfies an obvious recurrence, $b_m = 2b_{m-1}-b_{m-2}$, which encodes the fact that each term is the average of the term before it and the term after it. So now we just need to check the sequence $A_1, A_2, A_3, \dots$ also has this property. Luckily a lot of terms match up perfectly and we are just left with:

$$A_m+A_{m-2}-2A_{m-1} = 2mx_m + (3-2m)x_{m-1} $$

So in order for this recurrence relation to hold we just need to check that

$$2mx_m + (3-2m)x_{m-1} = 0$$

Which is easy to check by expanding $x_m = |\binom{\frac{1}{2}}{m}|$.

  • $\begingroup$ Thank you. I did not follow your hint, because it wasn't clear to me how to do it. $\endgroup$ – Yuriy S Apr 23 '16 at 17:37

Alright, I figured it out. First, we write the recurrence relation for the absolute value of the binomial coefficients:

$$x_m= \left| \left( \begin{matrix} \frac{1}{2} \\ m \end{matrix} \right) \right|=\frac{1/2 (1-1/2)(2-1/2)\cdots (m-1-1/2)}{m!}=\frac{m-3/2}{m}x_{m-1}$$


Next, we work with our system.

We subtract the equation number $m-2$ from the equation number $m-1$ to show:

$$x_1+x_2+\cdots + x_{m-2}=1-2(m-1)x_{m-1}$$

Now we add this equation to the equation number $m-1$ and obtain:

$$(m+1)x_1+(m+2)x_2+\cdots + (2m-2)x_{m-2}+(2m-2)x_{m-1}=m-2(m-1)x_{m-1}$$

$$(m+1)x_1+(m+2)x_2+\cdots + (2m-2)x_{m-2}=m-(4m-4)x_{m-1}$$

Now we use the RHS from this equation in the equation number $m$:


Finally we obtain:




Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.